Strategies for Increasing Beef Cattle Production under Dryland Farming Systems - Heather Burrow (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2019)
Integrated cattle and dryland farming systems in Indonesia use a range of crop residues and by products to feed cattle through intensive and extensive production systems. Intensive systems use stalls to house cattle and cut and carry feeding systems, primarily for fattening cattle. Under extensive systems, cattle are free‐grazing,and the systems apply only where greater land areas exist and they are used for breeding and fattening cattle. This paper therefore specifically focuses on the opportunities that exist to improve beef production in dryland farming systems in Indonesia. The best strategies for smallholder farmers in Indonesia to improve beef production require farmers to focus on profitability and use proven management strategies, including a) using adapted cattle breeds resistant/tolerant to environmental stressor, b) understanding the market preference; c) managing cattle breeding herds based on rainfall patterns, d) keeping good records on all aspects of breeding and fattening activities and e) adjusting stocking rates in extensive system to match the carrying capacity of the land.